Vancomycin-loaded bone cement bullet for treatment of chronic septic arthritis post ACL reconstruction surgery - Seo, Soon Teck; Teo, Seow Hui; Al-Fayyadh, Mohamed Zubair Mohamed; Ali, Mohamed Razif Mohamed; Ng, Wuey Min (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
The consequence of post-operative infection can be devastating despite its rare incidence. Common organisms causing post-operative infection are normal flora of the skin: Staphylococcus aureus and Staphylococcus epidermidis. Early diagnosis followed by arthroscopic debridement and antibiotic therapy with graft retention remains the main aim of treatment. However, there are certain cases where the infection persists despite early intervention. Vancomycin-loaded bone cement bullet inserted into bone tunnel can provide a high local concentration of vancomycin with bactericidal effect and low systemic complications to treat deep-seated infection. © 2019 UPM Press. All rights reserved.